2018
DOI: 10.1262/jrd.2017-042
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 inhibition affects cell cycle progression during early mouse embryo development

Abstract: Brusatol, a quassinoid isolated from the fruit of Bruceajavanica, has recently been shown to inhibit nuclear factor erythroid 2-related factor 2 (Nrf2) via Keap1-dependent ubiquitination and proteasomal degradation or protein synthesis. Nrf2 is a transcription factor that regulates the cellular defense response. Most studies have focused on the effects of Nrf2 in tumor development. Here, the critical roles of Nrf2 in mouse early embryonic development were investigated. We found that brusatol treatment at the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…Nrf2 mediates these responses primarily via increasing the transcription of www.nature.com/scientificreports www.nature.com/scientificreports/ antioxidant response element (ARE genes) [49][50][51] . Nrf2 has also been demonstrated to specifically regulate cell cycle transition from G2 to M phase via the cyclin B-CDK1 complex 35 , consistent with the effects on OECs we observed in the current study. We also showed that a known Nrf2 agonist, the plant flavonol quercetin, stimulated OEC proliferation, confirming that stimulation of Nrf2 enhance proliferation of these cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nrf2 mediates these responses primarily via increasing the transcription of www.nature.com/scientificreports www.nature.com/scientificreports/ antioxidant response element (ARE genes) [49][50][51] . Nrf2 has also been demonstrated to specifically regulate cell cycle transition from G2 to M phase via the cyclin B-CDK1 complex 35 , consistent with the effects on OECs we observed in the current study. We also showed that a known Nrf2 agonist, the plant flavonol quercetin, stimulated OEC proliferation, confirming that stimulation of Nrf2 enhance proliferation of these cells.…”
Section: Discussionsupporting
confidence: 91%
“…Other naphthoquinones have been shown to stimulate the activity of nuclear factor (erythroid-derived 2)-like 2(Nrf2) in other cell types 33,34 . Nrf2 regulates cell cycle transition from G2 to M phase 35 . We thus hypothesised that RAD618 may act on Nrf2 because our data showed that RAD618 stimulated cell viability by increasing the number of cells undergoing mitosis, consistent with as Nrf2 activation (crucial for G2 to M phase transition and thus mitosis).…”
Section: Rad618 Induces Cell Cycle Alterations In Gfp-moecs Consistenmentioning
confidence: 99%
“…Nrf2 mediates in several biological phenomenon, such as lipid metabolism [10], aging [13], and defense against oxidative stress in mammalian cells [14,15], including oocytes, and embryos [16,17]. Nrf2 mediates its antioxidant activity by translocating into the nucleus, where it binds to antioxidant response elements (AREs) to regulate the expression of genes related to the detoxication and antioxidant mechanisms [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 mediates its antioxidant activity by translocating into the nucleus, where it binds to antioxidant response elements (AREs) to regulate the expression of genes related to the detoxication and antioxidant mechanisms [18,19]. Nrf2 signaling has been proposed to be essential for oocyte maturation and embryo development in cows [16], mice [17], and pigs [8], because it counteracts conditions that are generated in response to ROS exposure. Additionally, some of these studies verified the role of the Nrf2 signaling pathway by administering brusatol-a quassinoid from Brucea javanica-that is recognized as a specific inhibitor of Nrf2, thereby preventing the activation of genes whose expression is driven by the AREs, even in conditions of high oxidative stress [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that activation of NFE2L2 in ethanol-exposed mouse embryos is involved in increased detoxifying and antioxidant enzymes (Harris & Hansen, 2012). Recently Lin et al (2018) reported that inhibition of NFE2L2 by brusatol prevents early mouse embryo development by affecting cell cycle progression from G2 to M Phase. The role of NFE2L2 has been investigated in a different cultural environment in bovine embryos that reached blastocyst stage (Gad et al, 2012).…”
Section: Introductionmentioning
confidence: 99%